The environmental monitoring system at the COSINE-100 experiment. (7th January 2022) - Kim, H.; Adhikari, G.; Barbosa de Souza, E.; Carlin, N.; Choi, J.J.; Choi, S.; Djamal, M.; Ezeribe, A.C.; França, L.E.; Ha, C.; Hahn, I.S.; Jeon, E.J.; et al.
Abstract: The COSINE-100 experiment is designed to test the DAMA experiment which claimed an observation of a dark matter signal from an annual modulation in their residual event rate. To measure the 1 %-level signal amplitude, it is crucial to control and monitor nearly all environmental quantities that might systematically mimic the signal. The environmental monitoring also helps ensure a stable operation of the experiment. Here, we describe the design and performance of the centralized environmental monitoring system for the COSINE-100 experiment.